1994
DOI: 10.2172/10147904
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of chloride, sulfate, and magnesium ions on hydrated Portland-cement paste

Abstract: Ground water with a high concentration of magnesium ion is known to cause deterioration to portland cement concretes. A proposed mechanism for this deterioration process published previously involves an approximate 1:1 replacement of Ca ions by Mg ions in the crystalline phases of hydrated cement. The current study was undertaken to determine which ions, among magnesium, chloride, and sulfate, cause deterioration; whether their deleterious action is individual or interdependent; and to relate this mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…As in our previous work (Poole et al, 1994) measurable strength loss occurred well before the detectable appearance of MSH, and deterioration is attributed to loss of calcium from hydrated cement phases, rather than to the formation of MSH.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…As in our previous work (Poole et al, 1994) measurable strength loss occurred well before the detectable appearance of MSH, and deterioration is attributed to loss of calcium from hydrated cement phases, rather than to the formation of MSH.…”
supporting
confidence: 78%
“…In our previous work (Poole et al, 1994), evidence for destruction of CSH was found in loss of more calcium from specimens than could be accounted for by total destruction of calcium hydroxide, and loss of strength occurred without formation of MSH. in the present study, additional evidence for loss of CSH was the appearance of magnesium silicate hydrate (MSH), a non-cementitious phase that forms at the expense of CSH.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…This series of concretes called Salado Mass Concrete (SMC) was refined through batching experiments and thermal and mechanical testing (Wakeley et al, 1994a). SMC component materials were also subjected to extensive geochemical tests (Poole et al, 1994;Wakeley et al, 1994b). The geochemical research showed that strength loss of cementitious solids in brines with strong concentrations of magnesium occurred by loss of calcium from cement hydration products, and not by direct replacement of calcium by magnesium, as has been reported elsewhere (Oberste-Padtberg, 1985;Bonen and Cohen, 1992).…”
Section: I Previous Wipp Research At the Wesmentioning
confidence: 99%